Association between interleukin-10 promoter gene polymorphisms and acute graft-versus-host disease after hematopoietic stem cell transplantation: A systematic review and meta-analysis. Issue 3 (April 2015) - Cho, In Hye; Song, Yun Kyoung; Kim, Myeong Gyu; Han, Nayoung; Kim, Therasa; Oh, Jung Mi
Abstract : Objectives: Interleukin-10 (IL-10) is an important immunomodulatory cytokine. The association between IL-10 promoter gene polymorphisms and acute graft-versus-host disease (aGVHD) risk is established; however, results of these studies remain inconclusive. We performed a meta-analysis to clarify the effects of IL-10 promoter gene polymorphisms on aGVHD risk. Methods: The authors searched MEDLINE, EMBASE, and Cochrane Library databases. Two independent authors extracted data, and the effects were estimated from an odds ratio (OR) with 95% confidence intervals (CIs). Subgroup and sensitivity analyses identified sources of heterogeneity. Results: Finally, a total of 11 studies encompassing 3588 recipients and 3221 donors were included to study IL-10 -1082 G > A, -819 C > T, and -592 C > A polymorphisms. IL-10 -819 CC genotype was associated with an increased aGVHD risk (grade I–IV: OR, 2.722 (95% CI, 1.360–5.450); grade II–IV: OR, 2.265 (95% CI, 1.015–5.053)). Furthermore, patients who received grafts from donors with an IL-10 -819 CC genotype experienced more frequent grade I–IV aGVHD (OR, 2.306 (95% CI, 1.168–4.551)). Recipients with IL-10 -592 CC genotypes were at increased risk for grade II–IV aGVHD (OR, 1.999 (95% CI, 1.230–3.250)). Together, this meta-analysis found that IL-10 -819 CC and -592 CC polymorphisms increased aGVHD risk. Discussion and Conclusion: This meta-analysis found the evidence that the IL-10 -819 CC and -592 CC genotypes in both recipients and donors increased the risk of aGVHD in allogeneic hematopoietic stem cell transplantation (HSCT) patients. These results contribute towards improving patient outcome through insight and rationale for individualized treatment strategies considering genetic determinants.